Landskapsanalys - Eriksson, Malin (2006)
This is a landscape character assessment of the landscape surrounding the suggested part of the Linnaean excursion path, Herbationes Danensis. It is situated between the two Linnaean heritage sites Linnés Hammarby and Funbo Lövsta south of Uppsala. This assessment is going to work as a support for planning projects in the area. It also gives suggestions about how to protect and develop the landscape.